MY SAY: Time to go green - Abd Razak, Dzulkifli (2009)
Everyone likes to be associated with something "sustainable" or, more fashionably, being "green". They do this without really understanding what this entails or working it out systematically on a wide platform. The risk then is that these are clichés used in a businessasusual fashion without any change in mindset, whereas the urgent task today is to quickly move away from the unsustainable way of life and habits that have taken the worst socioeconomic toll on the world since the Second World War.